Hemophagocytic lymphohistiocytosis associated with anaplasmosis - Tamara M Johnson (Journal of Global Infectious Diseases, 2017)
Hemophagocytic lymphohistiocytosis (HLH) is a hyperinflammatory syndrome characterized by unregulated macrophage and T-lymphocyte activation resulting in cytokine overproduction and subsequent histiocytic phagocytosis. Variant infections, particularly viruses have been postulated as the inciting factor for this potentially fatal disease. Herein, we will report a case of HLH associated with anaplasmosis.